1970
DOI: 10.1063/1.1673355
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Interactions in the Water Molecule: The Stretch–Stretch Interaction Force Constant of Water Molecules in Hydrogen-Bonded Systems

Abstract: A calculation is described for determining water molecule Frr force constants from observed HOD, H2O, and D2O vibrational frequencies. The calculations for water in the vapor and in the hydrates MnCl2·2H2O, FeCl2·2H2O, CoCl2·2H2O, and CuCl2·2H2O indicate a large increase in Frr with hydrogen bonding. Various contributions to Frr are considered, and its increase is attributed to an enhancement of the effective charge on water hydrogens with increased hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1973
1973
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This difference may be due to a smaller v,-v, splitting in the crystal than in the vapor or to the vibrations that contribute to the v, in-phase and out-ofphase bands not having near neighbors moving precisely in phase or out of phase respectively, or to a combination of both. Fifer and Schiffer (60) have shown that the v,-v, splitting of water molecules in several metal chloride hydrates is significantly smaller than in the vapor. While the hydrogen bonding in these salts may not be exactly comparable to that in ice I, the observation is consistent with the proposed assignment of ice I.…”
Section: Disordered Ice Icmentioning
confidence: 99%
“…This difference may be due to a smaller v,-v, splitting in the crystal than in the vapor or to the vibrations that contribute to the v, in-phase and out-ofphase bands not having near neighbors moving precisely in phase or out of phase respectively, or to a combination of both. Fifer and Schiffer (60) have shown that the v,-v, splitting of water molecules in several metal chloride hydrates is significantly smaller than in the vapor. While the hydrogen bonding in these salts may not be exactly comparable to that in ice I, the observation is consistent with the proposed assignment of ice I.…”
Section: Disordered Ice Icmentioning
confidence: 99%
“…Fe in equation (5) force constants (in N m-z) as given by Fifer & Schiffer (1970)" Fr=845"00; F,r=-10.47; F~,=16.72; F,= 75.40.…”
Section: V= 2v + 2ve=y~fxmentioning
confidence: 99%
“…However, the spectroscopic information is not detailed enough to make it possible to get information on the anharmonic part of the lattice perturbed intramolecular potential. We shall therefore assume, following Fifer & Schiffer (1970), that the anharmonicity is not significantly changed from what it is in the vapour.…”
Section: Introductionmentioning
confidence: 99%
“…However, the differences between Ba(ClO,),~H,O and water vapor are in qualitative agreement with the trend pointed out in ref. 27.…”
Section: Vibrations Of Water Moleculesmentioning
confidence: 99%
“…The harmonic frequencies so obtained are shown in Table 3. The nine frequencies were fitted using the four force constants to yield the calculated frequencies and force constants shown on the right hand side of (Table 3), much smaller than the gasphase value of about -0.1 (27), and this clearly reflects the smaller v,' -v,' separation. The value of Frr cannot be compared with those given by Fifer and Schiffer for other hydrates, because of their different treatment of the anharmonicity and the very low weight assigned to v,' in their fitting procedure.…”
Section: Vibrations Of Water Moleculesmentioning
confidence: 99%